Smoking Behaviour Among Adolescents: Community Health-Based Assistance at an Orphanage in Penang, Malaysia - Rahayu, Henik Tri; Rohmah, Anis Ika Nur; Wahyuningsih, Indri; Melizza, Nur; Bakar, Norasma; Pratiwi, Indah Dwi (Asian Journal of Community Services, 2024)
Tobacco use is still an unresolved welfare problem and is still a big problem in the world. The tendency to smoke will increase a person’s risk of developing respiratory, cardiovascular, and cancer. Adolescents are believed to try new things and copy others’ trends and behavior as part of their development stage. Therefore, they have great potential for smoking behavior in their adult life. This program aims to expand the understanding of adolescents living in orphanages about the dangers of smoking and understanding in planning to be smoke-free. We use an active participation method comprising a two-dimensional, colorful booklet as a learning media to deliver our community program. The result of this program is that participants have a moderate understanding of smoking and its complications in the future.